Clinical considerations of drug management in chronic cardiovascular and respiratory disorders in perioperative healthcare - Živanović Dejan B.; Rakanović Dragan M. (Srpsko lekarsko drustvo, 2018)
Introduction: Perioperative healthcare represents the care of the patient's health, before, during and after surgical intervention. There is a lot of clinical studies that confirm high incidence of cardiovascular and respiratory events during perioperative period, especially in patients who already suffer from chronic disorders of these organs and organ systems, which can be successfully prevented or minimized by adequate drug management. Methods: This paper is based on information from other reviews, clinical studies and textbooks, along with clinical experience, professional and theoretical considerations about cardiovascular and respiratory disorders' drug management in perioperative healthcare. Topics: This manuscript contains clinically relevant information about effects and adverse effects of intravenous and inhalational general anesthetics on the cardiovascular and respiratory system, as well as general and special recommendations for perioperative drug management in patients with hypertension, angina pectoris, cardiac arrhythmias, bronchial asthma, and chronic obstructive pulmonary disease (COPD). Conclusion: Postoperative recovery process may be seriously slowed down by perioperative cardiovascular and respiratory events, especially those which can directly endanger the patient's life before, during and after general anesthesia and surgery. The take-home message of this article is that most of the potential perioperative cardiovascular and respiratory complications can be successfully prevented by rational and individually tailored drug management in perioperative period.